Parental Substance Abuse As an Early Traumatic Event. Preliminary Findings on Neuropsychological and Personality Functioning in Young Drug Addicts Exposed to Drugs Early - Parolin, Micol; Simonelli, Alessandra; Mapelli, Daniela; Sacco, Marianna; Cristofalo, Patrizia (Frontiers in Psychology, 2016)
Parental substance use is a major risk factor for child development, heightening the risk of drug problems in adolescence and young adulthood, and exposing offspring to several types of traumatic event. First, prenatal drug exposure can be considered a form of trauma itself, with subtle but long-lasting sequalae at the neuro-behavioural level. Second, parents’ addiction often entails a childrearing environment characterised by poor parenting skills, disadvantaged contexts and adverse childhood experiences, leading to dysfunctional outcomes. Young adults born from/raised by parents with drug problems and who develop a Substance Used Disorder (SUD) themselves might display a particularly severe condition in terms of cognitive deficits and impaired personality function. This preliminary study aims to investigate the role of early exposure to drugs as a traumatic event, capable of affecting the psychological status of young drug addicts. In particular, it intends to examine the neuropsychological functioning and personality profile of young adults with severe SUDs who were exposed to drugs early in their family context. The research involved 3 groups each consisting of 15 young adults (aged 18-24): a group of inpatients diagnosed with SUDs and exposed to drugs early, a comparison group of non-exposed inpatients and a group of non-exposed youth without SUDs. A neuropsychological battery (Esame Neuropsicologico Breve-2), an assessment procedure for personality disorders (Shedler-Westen Assessment Procedure-200) and the Symptom CheckList-90-Revised were administered. According to present preliminary results, young drug addicts exposed to drugs during their developmental age were characterised by elevated rates of neuropsychological impairments, especially at the expense of attentive and executive functions; personality disorders were also common but did not differentiate them from non-exposed young people with SUDs. Alternative multi-focused prevention and intervention programs are needed for children of drug-misusing parents, addressing executive functions and adopting a trauma-focused approach.